Peranan Remaja Masjid dalam Penguatan Aqidah Remaja di Daerah Kelurahan Sukamaju - Nur Azizah Lubis (AL-HIKMAH:Jurnal Theosofi dan Peradaban Islam, 2022)
Teenagers as the nation's next generation are the only hope of the nation where if the teenager is a strong believer then he can solve the various problems he faces. Adolescents who are physically and mentally strong in dealing with various kinds of life's problems, will be people who are always useful for religion, homeland and nation. Society as a place for youth is well formed, one of which is through organizations in the community, namely mosque youth. This research uses qualitative research with observation, interview and documentation research techniques to obtain the resulting data. This research was carried out at the Ar Rahman Mosque Youth, Suka Maju Village. The results showed that 1) The role of mosque youth in strengthening adolescent aqidah in the Sukamaju area was in the low category. The lack of roles and participation carried out by the youth members of the mosque in carrying out activities in the youth of the mosque causes no motivation to be generated for the youth of the region like to progress. 2) The aqeedah in the youth association of mosques in this advanced area is still low based on the research conducted. In the last two years, the situation has decreased, slowly the number of members collected is starting to decrease, teenagers are starting to be lazy to carry out the practices that they have been able to do at the mosque, such as praying in congregation, reading the Koran at sunset, conducting regular recitations, filling out materials and lectures.